The Quality of Machine Translation Assessment On Gender Markers Lingual Units - Hapni Nurliana H.D Hasibuan (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2021)
Machine Translation (MT) is one of the most advanced and elaborate research fields within Translation Technology, the quality of MT output has always been a great concern, and MT evaluation is a popular research topic. This research aims to assess the quality translation on the gender markers lingual unit of the Arabic short story